India unbound - Das, Gurcharan (New Delhi, 2000)
India Unbound is the riveting story of a nation$1 (Bs rise from poverty to prosperity and the clash of ideas that occurred along the way. Gurcharan Das examines the highs and lows of independent India through the prism of history, his own experiences and those of numerous others he has met$1 (Bfrom young people in sleepy UP villages to chiefs of software companies in Bangalore. Defining and exploring the new mindset of the nation, India Unbound is the perfect introduction to contemporary India.s
Keywords: India - Economic transformation